ХТИВЕ ДІВЧИСЬКО (the text is only in Ukrainian) (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
Ісабель Альєнде "Оповідки Єви Луни" (the text is only in Ukrainian)translated from Spanish by Olga Pihuly